2019
DOI: 10.3390/agriculture9070161
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Technical Efficiency and Its Potential Determinants among Small-Scale Coffee Farmers in Rwanda

Abstract: Coffee production is the main economic activity for smallholder farmers in Rwanda; it is also a major export crop. However, Rwandan coffee production has been facing structural changes with a significant decline in production. Considering the importance of the coffee sector to rural livelihoods and its potential role in export earnings, there is a need to ensure that small-scale coffee farmers efficiently use scarce resources in their production activities. Thus, this study estimates the technical efficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
29
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
17
29
1
4
Order By: Relevance
“…On the other hand, 1 percent increase in frequency of irrigation for tomato production will lead to a 0.124 percent increase in tomato production. This result is consistent with the findings of Khan et al (2010) and Ngango et al (2019).…”
Section: Stochastic Production Frontier Functionsupporting
confidence: 94%
See 2 more Smart Citations
“…On the other hand, 1 percent increase in frequency of irrigation for tomato production will lead to a 0.124 percent increase in tomato production. This result is consistent with the findings of Khan et al (2010) and Ngango et al (2019).…”
Section: Stochastic Production Frontier Functionsupporting
confidence: 94%
“…Or the mean of TE indicates that if sample households operated at full efficiency level, they would increase their output by 19.3% using the existing resources and level of technology. This mean score is in line with a similar study conducted by Ngango et al (2019) who observed a mean technical efficiency level of 82% amongst coffee growers in the Rwanda. As indicated in the table technical efficiency ranges from 0.25 to 0.977.…”
Section: Distribution Of Te Scores and Yield Gap Due To Inefficiency supporting
confidence: 92%
See 1 more Smart Citation
“…This shows that the land used for sweet potato farming is land that lacks soil nutrients. These results are consistent with findings from Ngango and Kim [10].…”
Section: B Estimation Of Production Functionsupporting
confidence: 93%
“…Souza et al (2017) discutem que, em detrimento de imperfeições de mercado (por exemplo a falta de informações e do acesso à educação), a assistência técnica e extensão rural podem ser vistas como não importantes na eficiência produtiva, sendo uma conclusão equivocada. Ngango & Kim (2019) afirmam que a educação e serviços de extensão, dentre outros fatores, possibilitam o aumento da eficiência técnica da produção de café.…”
Section: Resultsunclassified